Construction of Party Political Narratives in the 2024 DKI Jakarta Regional Head Election (Pilkada) Framing Analysis on CNNIndonesia.com and Okezone.com: Konstruksi Narasi Politik Partai dalam Pemilihan Kepala Daerah (Pilkada) DKI Jakarta 2024 Analisis Framing pada CNNIndonesia.com Dan Okezone.com - candelia, dera; Nurdin, Ali (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The media employs strategies in news writing to become the primary choice for readers. Ahead of the 2024 Regional Head Elections (Pilkada), media outlets are competing to present news on the subject, including CNNIndonesia.com and Okezone.com. This study aims to understand how political narratives and the roles of parties are constructed by CNNIndonesia.com and Okezone.com in their coverage of the 2024 DKI Jakarta Pilkada. The study adopts a constructivist approach, focusing on how the media constructs the social reality of the 2024 DKI Jakarta Pilkada. The research employs Robert N. Entman's framing analysis, which includes four elements: define problems, diagnose causes, make moral judgments, and treatment recommendation. Data collection was carried out through documentation obtained from CNNIndonesia.com and Okezone.com news reports within the period of August 26, 2024. The results reveal that in the define problems stage, CNNIndonesia.com portrays PDIP's decision as a political maneuver based on party loyalty, while Okezone.com focuses on its controversial aspects. In the diagnose causes stage, CNNIndonesia.com highlights internal party factors and ideological interests, whereas Okezone.com emphasizes Megawati's central role in decision-making. The make moral judgment element in both media shows that PDIP prioritizes cadre loyalty over the electability of external figures, albeit from different perspectives. Lastly, in the treatment recommendation stage, CNNIndonesia.com suggests transparency to reduce negative perceptions, while Okezone.com stresses the importance of further explanation from PDIP to maintain public support. These findings indicate that media framing not only shapes public opinion but can also influence local political dynamics by crafting specific narratives tailored to each media outlet's focus. This study underscores the critical role of media in shaping public perceptions and opinions about candidates and party decisions, potentially impacting the outcome of the 2024 DKI Jakarta Pilkada.